Faktor-faktor yang Berpengaruh terhadap Permintaan Daging Babi Segar di Kota Kupang: Factors Influencing Demand For Fresh Pork In The City Of Kupang - Manu Ndun, Shelin Audina; Lole, Ulrikus R.; Makandolu, Solvi M; Ratu, Maria R.D; Sabat, Diana M. (Universitas Nusa Cendana, 2024)
This study seeks to examinel the demand for pork and the various elements that impact meat demand. The process of determining samples invovels two stags. The initial step was purposelfuly selelcting the sample subdistricts. The second phase ilnvolveld sellelctilng a samplel of 90 consumelrs iln a non-proportilonal random melthod. Thel data was analyzeld iln a descriptive manner, incorporating both quantitative and qualiltative approaches. The method employed for analysis ils quantitative, utilizing correlation and regression analysis through the Cobb-Douglas rank function. This approach allows for a detailed examination of the data with a focus on relationships and trends. It's a powerful tool for drawing meaningful insilghts from the information at hand. The results of the correlation analysis show that there are five factors that have a strong relationship to the demand for pork (Y), namelly the price of chicken meat (X2), eggs (X4), incomel (X6), family responsibilities (X7) and education level (X8). The results of the regression analysis show that there are factors that influence the demand for pork in the city Kupang is Y=-12.561 X20,846 X4=1.146 X60,569 X70,104 X80,191. Factors that have a very real influence on the demand for fresh pork in Kupang City are the price of chicken meat (b2), the price of eggs (b4) and income (b6), with R2=63,7% Tujuan dari penelitian ini adalah untuk memeriksa permintaan daging babi serta faktor-faktor yang memengaruhi permintaan daging babi. Contoh dipilih dalam dua tahap. Kelurahan contoh dipilih secara purposif pada tahap pertama. Kemudian, sembilan puluh konsumen contoh dipilih secara acak selcara non proporsional. Analisis data dilakukan secara deskriptilf, baik kualitatif maupun kuantitatif. Analisis kuantitatif menggunakan fungsi brpangkat Cobb-Douglas untuk menganalsis korelasi dan regresi. Hasil analisis korelasi menujukkan bahwa terdapat lima faktor yang memililki hubungan kuat terhadap permintaan daging babi (Y), yaitu harga daging ayam (X2), telur (X4), pendapatan (X6), tanggungan keluarga (X7), dan tingkat pendidikan (X8). Hasil analisis regresi menunjukkan bahwa faktor-faktor yang berpengaruh terhadap permintaan daging babildi Kota Kupang adalah Y=-12.561 X20,846 X4=1.146 X60,569 X70,104X80,191 faktor-faktor yang berpengaruh sangat nyata terhadap permintaan daging babi segar di Kota Kupang adalah harga daging ayam (b2), harga telur (b4), dan pendapatan (b6) dengan R2= 63,7%.